Optimization of nSiO2-Filled RTV Silicone Rubber Coatings for Enhanced High Voltage Outdoor Insulator Performance - Nalendra, Agustinus D.; Rachmawati; Alifianda, Aulia R.; Permatasari, Fitri A.; Suwarno (Emerging Science Journal, 2025)
This paper presents the experimental results of leakage current testing on nanosilica (nSiO₂)-filled room-temperature vulcanized (RTV) silicone rubber (SiR) coatings for outdoor insulators. Nanosilica composition is prepared based on the optimization results of surface hydrophobicity, surface resistivity, and relative permittivity of the RTV SiR matrix with varying nSiO2 contents. The study found that the insulator with a 4 wt.% nSiO₂-filled RTV SiR coating had the highest surface resistivity, better hydrophobicity, and higher permittivity compared to the unfilled RTV SiR coating. Leakage current tests are performed under several conditions (dry, clean fog, and salt fog) to evaluate the insulation characteristics of the modified RTV SiR coating applied on an actual high-voltage insulator. The results indicate that the 4 wt.% nSiO2-filled RTV SiR-coated insulator significantly reduces the leakage current magnitude and Total Harmonic Distortion (THD) when compared to that of the uncoated as well as to that of unfilled RTV SiR-coated insulators. Under all fog conditions, the 4 wt.% nSiO2-filled RTV SiR-coated insulator with a polluted surface showed the smallest leakage current THD percentage of all insulator samples. Additionally, the cross product of the leakage current magnitude and THD is also calculated to determine the condition of the insulator. The cross-product results show that the 4 wt.% nSiO₂-filled RTV SiR-coated insulator is more effective at reducing it under dry conditions, with a reduction range of 68%–81% compared to the uncoated isolator and 70%–77% compared to the unfilled RTV SiR-coated isolator. This study shows the effectiveness of RTV silicone rubber coating material with nSiO2 filler particles in reducing the magnitude of leakage current and harmonics in polluted environments.